Given:
The center of the circle is the point ( 3, 2 )
And the point on the circle is ( 4, 3 )
To write the equation of the circle, we need to find the radius
The radius = the distance between the center and the point on the circle
so, the radius is the distance between ( 3, 2) and ( 4, 3)
So,
![\begin{gathered} r=d=\sqrt[]{(x_2-x_1)^2+(y_2-y_1)^2} \\ r=\sqrt[]{(4-3)^2+(3-2)^2^{}}=\sqrt[]{1+1}=\sqrt[]{2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hz1tu2rqfpfrw0rhbrq6c92pdpyk66x3tg.png)
The general equation of the circle is:
![(x-h)^2+(y-k)^2=r^2](https://img.qammunity.org/2023/formulas/mathematics/college/5s77z5lwu6jnvb5vkwanu2jvhq5sh1qkc3.png)
Where (h, k) is the coordinates of the center of the circle, r is the radius
So,
![\begin{gathered} (h,k)=(3,2) \\ r=\sqrt[]{2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/eszs0fcu3w5wfewgaz9sbip33pw6rcg1dh.png)
so, the equation of the circle will be:
![(x-3)^2+(y-2)^2=2](https://img.qammunity.org/2023/formulas/mathematics/college/6vpnk0cteivfcltk07vpakmuokxbfdav3k.png)